Artificial Intelligence Assisted Prediction of Brivaracetam Treatment Response: A Future Perspective - Sakshi Shelke; Dr Vinayak Gaware (Asian Journal of Pharmaceutical Research and Development, 2026)
Brivaracetam is a third-generation antiseizure medication that selectively targets synaptic vesicle protein 2A (SV2A) and has demonstrated significant efficacy in the management of focal epilepsy. Despite its favorable pharmacological profile and improved tolerability compared to earlier agents, a substantial proportion of patients exhibit variable therapeutic responses. This unpredictability highlights a critical gap in epilepsy management, where treatment selection still relies heavily on empirical approaches. Artificial Intelligence (AI), particularly machine learning techniques, has emerged as a transformative tool capable of integrating complex, multidimensional datasets to predict individualized drug responses. This review discusses the pharmacological basis and clinical efficacy of brivaracetam, examines current challenges in predicting treatment outcomes, and explores the potential of AI-driven models to enhance precision medicine in epilepsy. Future perspectives emphasize the integration of multimodal data, real-world evidence, and advanced computational techniques to optimize therapeutic strategies.